2021
DOI: 10.2147/jpr.s303186
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain: What Does It Mean? A Review on the Use of the Term Chronic Pain in Clinical Practice

Abstract: Chronic pain is nowadays used as an umbrella term referring to a wide range of clinical conditions, such as fibromyalgia, migraine, or long-standing pain states without actual known causes. However, labeling a patient's clinical condition with the term "chronic pain", when dealing with pain lasting longer than 3 months, might be misleading. This paper aims at analyzing the possible pitfalls related to the use of the term "chronic pain" in the clinical field. It appears, indeed, that the term "chronic pain" sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 47 publications
(68 reference statements)
0
38
0
3
Order By: Relevance
“…A great deal of research has been dedicated to the neurological aspects of FM pain, with various studies describing the brain areas involved in its perception (32)(33)(34) and their associations with specific metabolites (35). Interestingly, Muller et al found that the pattern of brain activation is not due to functional or structural alterations in the areas involved in acute pain (36), once again underlining that chronic pain is not just "longer-lasting pain" (37).…”
Section: Pain Neurophysiologymentioning
confidence: 99%
“…A great deal of research has been dedicated to the neurological aspects of FM pain, with various studies describing the brain areas involved in its perception (32)(33)(34) and their associations with specific metabolites (35). Interestingly, Muller et al found that the pattern of brain activation is not due to functional or structural alterations in the areas involved in acute pain (36), once again underlining that chronic pain is not just "longer-lasting pain" (37).…”
Section: Pain Neurophysiologymentioning
confidence: 99%
“…Chronic NP is, like all types of chronic pain, a complicated matter. The discussion has reached a point where the term “chronic pain” is now questioned, and other definitions have been suggested [ 4 , 5 ]. This study uses persistent or recurrent pain synonymously for chronic pain, because studies have shown that chronic pain varies in intensity and most often is episodic [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain subjects experience continuous recurring pain at monthly or yearly intervals, which makes it impossible to carry out ordinary daily activities [ 19 ]. Current therapies for chronic pain included nonsteroidal anti-inflammatory drugs, opioids, antidepressants, and myorelaxant agents.…”
Section: Discussionmentioning
confidence: 99%